1998
DOI: 10.2337/diabetes.47.12.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin-induced diabetes and of insulin treatment on homocysteine metabolism in the rat.

Abstract: An elevation in the concentration of total plasma homocysteine is known to be an independent risk factor for the development of vascular disease. Alterations in homocysteine metabolism have also been observed clinically in diabetic patients. Patients with either type 1 or type 2 diabetes who have signs of renal dysfunction tend to exhibit elevated total plasma homocysteine levels, whereas type 1 diabetic patients who have no clinical signs of renal dysfunction have lower than normal plasma homocysteine levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
136
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(170 citation statements)
references
References 0 publications
30
136
1
3
Order By: Relevance
“…Hyperhomocysteinaemia is known to be associated with impaired endotheliumdependent vasodilation [36,37]. Plasma homocysteine concentrations were, however, lower in the diabetic than in the control rats, as described previously [38], and were not influenced by treatment with 5-MTHF. Accordingly, folate has been shown to restore endothelial dysfunction during a methionine load test in healthy volunteers without affecting the rise in plasma homocysteine concentrations [17].…”
Section: Basalmentioning
confidence: 62%
“…Hyperhomocysteinaemia is known to be associated with impaired endotheliumdependent vasodilation [36,37]. Plasma homocysteine concentrations were, however, lower in the diabetic than in the control rats, as described previously [38], and were not influenced by treatment with 5-MTHF. Accordingly, folate has been shown to restore endothelial dysfunction during a methionine load test in healthy volunteers without affecting the rise in plasma homocysteine concentrations [17].…”
Section: Basalmentioning
confidence: 62%
“…Studies in our laboratory have shown that plasma homocysteine is decreased in the streptozotocin-diabetic rat (a model for Type 1 diabetes mellitus). Insulin treatment increased plasma homocysteine in these diabetic animals (9). We have also shown that enzyme activities of the hepatic transsulfuration pathway are increased during uncontrolled diabetes.…”
mentioning
confidence: 60%
“…This shift is also reflected in other 270 gluconeogenic states, such as diabetes. We and others have demonstrated that a diabetic state or 271 administration of synthetic glucocorticoid compounds has a major impact on methyl group and 272 homocysteine metabolism [23][24][25][26][49][50][51][52]. A consistent finding from these reports is a reduction 273 in circulating homocysteine concentrations owing to an increase in folate-independent 274 remethylation (i.e., BHMT) and catabolism of homocysteine through the transsulfuration 275 pathway.…”
mentioning
confidence: 88%